Research on transfer case transmission power of heat load characteristics. (7th August 2019) - Wang, Yu-ming; Wang, Qi-dong; Chen, Li-qing; Gu, Tian-yi
The performance of transfer case as an essential component of intelligent four-wheel drive is studied mostly from the perspective of mechanical transmission. However, friction heat during the transmission of power is rarely discussed. In this paper, a multi-plate clutch model is constructed based on heat load characteristics. And a performance simulation model in Matlab/Simulink is built to analyse the influence of friction disc on the dynamic transfer characteristics from aspects of structural dimension, material property and working condition. Then, the thermal load characteristics of the multi-plate clutch are analysed. Results show that the heat load has a great influence on the friction coefficient and the viscosity of the lubricating oil. In summary, this paper verifies the important role of heat load in the working process of transfer case, and the operating characteristic change rules during connecting process are discussed, which can be provided as a theoretical basis for the designing of transfer case.